Efficacy of Cardiopulmonary Resuscitation in the Supine Position With Manual Displacement of the Uterus Versus Lateral Tilt Using a Firm Wedge: A Manikin Study. Issue 3 (September 2015) - Butcher, M.; Ip, J.; Bushby, D.; Yentis, S.M.
Abstract : ( Anaesthesia . 2014;69(8):868–871)